The Act of PMTCT Program to Decrease the Numbers of HIV in Situbondo Regency - Lea Ingne Reffita; Byba Melda Suhita; Indasah Indasah (Humanistic Network for Science and Technology (HNST), 2018)
PMTCT is an effort to prevent the occurrence of HIV infection in women and prevent HIV transmission from pregnant mother to baby. The number of women infected with Human Immunodeficiency Virus (HIV) from year to year has increased, along with the increasing number of men who have unprotected sexual intercourse, which will transmit HIV to their sexual partners. The purpose of this research is to explore the implementation of PMTCT program in Situbondo regency. The research design used was qualitative research with phenomenology approach. Data collection used indepth interview technique with semi-structured question. Sampling technique in this research used purposive sampling with the sample size of 8 informants from 17 informants. From the result of the research showed that the implementation process of PMTCT program influences the development of PMTCT program in every year and will cause positive impact for both health worker and pregnant woman. In the process of PMTCT program implementation was influenced by several factors, such as, there were factors that support from the implementation process of PMTCT program as well as heading off the factors. From these inhibiting factors, several strategies were used to support the PMTCT program. Based on the research, it is necessary to conduct further research on the implementation process of PMTCT program Keywords: PMTCT (prevention of mother to child HIV transmission); Human Immunodeficiency Virus (HIV)